PENGGUNAAN BAHAN ECO-FRIENDLY SEBAGAI MEDIA PEMBELAJARAN BAHASA INGGRIS YANG MENYENANGKAN DI MTS AL-JIHAD SAMBOJA: Using Eco-Friendly Materials as the Media for Fun English Learning in MTs Al-Jihad Samboja - Sanhadi Rahayu, Famala Eka; Setyoko, Aris; Valiantien, Nita Maya; Hanum, Irma Surayya; Hilal, Hikmatul Fajar Syamsu; Musthofa, Dwi (Jurnal Ruhui Rahayu: Jurnal Pengabdian Masyarakat Ilmu Humaniora, 2023)
This community service program aims to improve students’ interests and attitudes toward English language learning and promote environmental awareness, especially in reusing plastic bottles to minimize microplastic trash. The community service program is a seminar with an interactive lecture method, a Games Tournament, and a project-based learning method. To measure students’ interest and attitude toward English language learning, they are requested to fill out the questionnaire before and after the activity to see how it changes. The questionnaire results showed a significant improvement in students’ interests and attitudes to English language learning, which is caused by environmental and psychological change. Students are believed to be more encouraging in the activity because they feel safe to express their idea in class after having their awareness of the learning process raised. Therefore, a fun circumstance and safe atmosphere are keys to success in learning English.